2016
DOI: 10.35196/rfm.2016.3.323-330
|View full text |Cite
|
Sign up to set email alerts
|

Análisis De La Diversidad Genética De Agaves Mezcaleros Del Centro De México

Abstract: En el Altiplano Potosino, un ecosistema árido y semiárido, Agave salmiana Otto Salm Dick ssp. crassispina (Trel Gentry) es una especie utilizada para la recolección de insectos comestibles y para producción de mezcal, bebida alcohólica tradicional con denominación de origen. El aprovechamiento para producción de mezcal de las poblaciones silvestres de Agave salmiana ssp. crassispina carece de un sistema de explotación basado en el conocimiento biológico de la especie. Esto tiene efectos demográficos, y a su ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…crassispina in San Luis Potosí. In that study, AFLPs were used as the molecular marker, and the authors found high genetic diversity (He = 0.403), no population structure (F ST = 0) and high gene flow (tending toward infinity) [28]. The third and fourth studies were of the A. hookeri species in the P´urhepecha highlands in Michoacán, Mexico; nuclear microsatellites showed low population genetic diversity (He = 0.485) compared to the most likely wild ancestor (A. inaequidens He = 0.704-0.733), strong population structure (F ST = 0.28) and fixation of heterozygotes, a genetic trait associated with the selection of favorable genotypes in crops [16,20].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…crassispina in San Luis Potosí. In that study, AFLPs were used as the molecular marker, and the authors found high genetic diversity (He = 0.403), no population structure (F ST = 0) and high gene flow (tending toward infinity) [28]. The third and fourth studies were of the A. hookeri species in the P´urhepecha highlands in Michoacán, Mexico; nuclear microsatellites showed low population genetic diversity (He = 0.485) compared to the most likely wild ancestor (A. inaequidens He = 0.704-0.733), strong population structure (F ST = 0.28) and fixation of heterozygotes, a genetic trait associated with the selection of favorable genotypes in crops [16,20].…”
Section: Introductionmentioning
confidence: 98%
“…crassispina in San Luis Potosí. In that study, AFLPs were used as the molecular marker, and the authors found high genetic diversity (He = 0.403), no population structure (F ST = 0) and high gene flow (tending toward infinity) [ 28 ]. The third and fourth studies were of the A .…”
Section: Introductionmentioning
confidence: 99%
“…crassipina in San Luis Potosí. In that study, AFLPs were used as the molecular marker, and the authors found high genetic diversity (He = 0.403), no population structure (F ST = 0) and gene ow were high (tending toward in nity) [27]. The third and fourth studies were of the A. hookeri species in the P´urhepecha highland in Michoacán, Mexico; nuclear microsatellites showed low population genetic diversity (He = 0.485) compared to the most likely wild ancestor (A. inaequidens He = 0.704-0.733), strong population structure (F ST = 0.28) and xation of heterozygotes, a genetic trait associated with the selection of favorable genotypes in crops [16,20].…”
Section: Introductionmentioning
confidence: 98%